Amos' Attitude toward Poverty: An African Perspective - Wafawanaka, Robert (African Journal of Biblical Studies, 2003)
W. examines three terms for poverty (ʼbywn, dl, ʻnwym) and the language of oppression as used in Amos. The inclusio of 2:6-7 and 8:4-6 brackets an inner inclusio which hinges on 5:11-12, both inclusios highlighting the central message of Amos that debt slavery and legal injustice are at the heart of the nation's sin. The rhetorical technique of reversal in 2:4-8 (judgment turned against Judah and Israel) is utilized again at the end of the book (9:11-15), where another reversal highlights a message of hope. The book's message of social justice for the poor makes the same appeal to the affluent today as it did to those in Amos' time. [Abstracted by: John W. Hilber] Abstract Number: OTA28-2005-FEB-369
Keywords: Minor Prophets